Program Kemitraan Masyarakat pada Ibu PKK Kelurahan Tidore sebagai Upaya Pencegahan Stunting - Gaiska Faradila Patras; Ashara Insavila Achmad; Sahdan Patras; Nyctagina Mandahari; Wendy Alexander Tanod; Yana Sambeka; Eko Cahyono; Frets Jonas Rieuwpassa; Frans Gruber Ijong; Novalina Maya Sari Ansar (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The purpose of this community service activity was to transfer knowledge to the PKK women of Tidore Village. The stages of implementing community service activities were observation and initial interviews, determining solutions to partner problems, implementing activities, and evaluating. There were two materials provided in this activity, namely “The Impact of Nutritional Inadequacy Which Can Lead to Stunting Conditions” and “Nutritional Benefits of Fish and Processing Techniques.” In addition to providing material, there was also a practice of diversifying fishery products from Decapterus sp. into high-value processed products, namely dragon leg, which was expected to increase fish consumption and contribute to reducing stunting rates. According to the evaluation results, this service activity could increase the knowledge and skills of PKK women about the benefits of fish consumption for child development and pregnant women. Activities like this are expected to continue to be carried out regularly so as to contribute to the prevention of stunting in the region.